Myths and misconceptions of intimate partner violence among sexual and gender minorities: a qualitative exploration - Kurbatfinski, Stefan; Letourneau, Nicole; Marshall, Susanne; McBride, Dawn; Novick, Jason; Griggs, Keira; Perrotta, Arielle; Daye, Morgan; McManus, Carrie; Nixon, Kendra (Frontiers in Sociology, 2024)
BackgroundIntimate partner violence (IPV), referring to different forms of violence or abuse between two or more intimate partners, negatively impacts physical and mental health, performance in various settings, and familial functioning, leading to long-term adverse outcomes. Sexual and gender minority (SGM) individuals tend to experience similar or greater frequencies of IPV compared to their cisheterosexual counterparts. Stigma and discrimination toward sexual and gender diversity can lead to myths and misconceptions about relationship dynamics among SGM individuals, which can contribute to IPV occurrence within the community. This study sought to: (1) develop a compendium of myths and misconceptions that SGM individuals exposed to IPV and relevant service providers shared they encountered; (2) describe the impacts of these myths and misconceptions on SGM individuals experiencing IPV; and (3) make recommendations to address these myths and misconceptions.MethodsThis qualitative study used data from a larger project focused on SGM IPV where SGM individuals who experienced IPV (n = 18) and service providers who supported SGM individuals experiencing IPV (n = 8) were interviewed using semi-structured formats. Thematic content analysis and inductive approaches were used to identify and organize findings into themes and subcategories.FindingsFive major themes related to SGM IPV myths and misconceptions were identified, touching on aspects including, but not limited to, SGM IPV prevalence, prescribed gender roles and expectations, and societal factors. Impacts and recommendations are also discussed.SignificanceThis appears to be the very first in-depth study describing myths and misconceptions that SGM individuals and relevant service providers have encountered in regard to SGM IPV, helping to promote understanding of SGM intimate partner relationships with particular relevance to public health and social services policies.